The Historical Fact Bissu South Sulawesi in the Novel Tiba Sebelum Berangkat (Study Literature Mimetic) - Hariyono, Saharul; Nurhadi (Mediterranean Journal of Social Sciences, 2020)
The purpose of this study describes historical fact background character of bissu and describes historical fact of the life character of bissu. The historical aspect in question is how history is rewritten in the novel Tiba Sebelum Berangkat. This study is a qualitative descriptive study, using a mimetic approach is based on Plato's perspective. The validity of the data used to observe the semantic validity of the data units of words, sentences, discourse, dialogue, which is found in the novel. Reliability data using interrater and interrater. Reliability interrater used reading and reviewing repeatedly to find the consistency of the data while interrater had discussions with people who can appreciate literature. Analysis of the data used is content analysis to determine the content and meaning contained in the novel Tiba Sebelum Berangkat. Results in this study, first, historical fact background character of bissu includes: bissu as the traditional ceremonial leader indigenous; stage becomes bissu; the hierarchy of community bissu. Second, historical fact of the life character of bissu includes: bissu becomes the center of Operation Tobat DI/TII; syncretism of bissu and Islamic religion; bissu title pilgrim to Mecca; government intervention against bissu; now bissu as beauty salon worker; novel Tiba Sebelum Berangkat as a form of social criticism. The findings based on that novel have a relationship with bissu real life. Thus, the novel Tiba Sebelum Berangkat contains historical narrative bissu life in South Sulawesi. The impacts resulting from this research can reveal the historical facts that occur in the content of the novel.